Advokat sebagai Mediator di Luar Pengadilan - Dedy Syahputra; Rizki Zil Ikram Rambe; Fauziah Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The implementation of mediation in court still seems formalistic, and can result in a slower case settlement process. Sometimes the decision also cannot produce a decision that benefits both parties and therefore the Advocate is present as a mediator outside the court who can be relied on and transparent. The method used in this research is the normative juridical method where the research is carried out based on the main legal material by examining the theories, concepts, legal principles and laws and regulations related to this research. , where research is reviewed from several bibliography and then analyzed carefully. Research shows that Advocates as Mediators outside the court are very good and are very much needed by the community because they can help the community in resolving disputes easily and without new conflicts. Keywords: Violation, Code Out of court, Advocate